Estradiol Synthesis and Release in Cultured Female Rat Bone Marrow Stem Cells. (26th December 2012) - Zhang, Dalei; Yang, Bei; Zou, Weiying; Lu, Xiaying; Xiong, Mingdi; Wu, Lei; Wang, Jinglei; Gao, Junhong; Xu, Sifan; Zou, Ting
Abstract : Bone marrow stem cells (BMSCs) have the capacity to differentiate into mature cell types of multiple tissues. Thus, they represent an alternative source for organ-specific cell replacement therapy in degenerative diseases. In this study, we demonstrated that female rat BMSCs could differentiate into steroidogenic cells with the capacity for de novo synthesis of Estradiol-17 β (E2) under high glucose culture conditions with or without retinoic acid (RA). The cultured BMSCs could express the mRNA and protein for P450arom, the enzyme responsible for estrogen biosynthesis. Moreover, radioimmunoassay revealed that BMSCs cultured in the present culture system produced and secreted significant amounts of testosterone, androstenedione, and E2. In addition, RA promoted E2 secretion but did not affect the levels of androgen. These results indicate that BMSCs can synthesize and release E2 and may contribute to autologous transplantation therapy for estrogen deficiency.